ANALISIS KARAKTERISTIK ELEKTRIK AIR LAUT TERSARING SEBAGAI SUMBER ENERGI ALTERNATIF BERKELANJUTAN (SUSTAINABLE ENERGY) - Edward Jannert; Gurum Ahmad Pauzi; Amir Supriyanto (Jurnal Teori dan Aplikasi Fisika, 2018)
The electrical characteristics of filtered seawater can be determined by using Cu-Zn electrode pairs. Seawater is filtered by using a 1 micron sediment filter. Measurement of electrical characteristics of water is carried out using a 3 watt DC LED load and when the load is removed. The electrolyte cell consists of 40 cells, which are arranged in series and parallel with 300 ml per cell. Tool testing is carried out for 144 hours with 6 times electrolyte filling every 24 hours. The test results show that the longer the tool is used, the more electrical characteristics produced will be decreasing. The produce of maximum voltage (Vbl) by seawater is not filtered with a series of 31.5 V. The produce of maximum power (P) by seawater is not filtered with a series of 101.1 mW. The produce of maximum illumination by seawater is not filtered with a series of 426.4 Lux, the duration of the light is 8 hours. Despite the produce of maximum illumination by filtered seawater with a series of 319.7 Lux series, the duration of the light is 11 hours.